A JUDICIAL NICHE FOR NECESSITY − IS IT REALLY NECESSARY? − Rieck v Crown Chicken (Pty) Ltd t/a Rocklands Poultry [2006] SCA 127 (RSA) - André Mukheibir (Obiter, 2022)
Our courts have played strange games in recent years with the elements of delict, the most frequent being that of changing the order of negligence and wrongfulness in the case of an omission and testing for the former before deciding on the latter. (Eg, including, but, not limited to, Gouda Boerdery Bk v Transnet 2005 5 SA 490 (SCA); Eskom Holdings Ltd v Hendricks 2005 5 SA 503 (SCA); Coetzee v Fourie 2004 6 SA 485 (SCA); Minister of Safety and Security v Van Duivenboden 2002 6 SA 431 (SCA); Sea Harvest Corporation (Pty) Ltd v Duncan Dock Cold Storage Ltd 2000 1 SA 827 (SCA); Mkwatsha v Minister of Defence 2000 1 SA 1 1004 (SCA); and Goldstein v Cathkin Park Hotel 2000 4 SA 1091 (SCA).) The latest addition to the conceptual confusion emanating from the Supreme Court of Appeal is that of equating the test for wrongfulness with that of negligence, because of the objective nature of both these tests. This approach, it is submitted, is incorrect because it seems to ignore the fact that these two elements fulfil different conceptual functions. Wrongfulness is concerned with determining the reasonableness of the conduct, whereas fault looks at the blameworthiness of the perpetrator (see the discussion by Neethling, Potgieter and Visser Law of Delict 5ed (2006) 141-143 of the distinction between these two elements).